Microbiota analysis of perimenopausal women experiencing recurrent vaginitis in conjunction with urinary tract infection - Yingying Bi; Yuezhu Wang; Wu Li; Yuhang Chen; Jinlong Qin; Huajun Zheng (BMC Microbiology)
Abstract Background Recurrent vaginitis in conjunction with urinary tract infection (RV/UTI) in perimenopausal women is a common clinical condition that impacts both doctors and patients. Its pathogenesis is not completely known, but the urogenital microbiota is thought to be involved. We compared the urogenital and gut microbiotas of perimenopausal women experiencing RV/UTI with those of age-matched controls to provide a new microbiological perspective and scheme for solving clinical problems. Results Fifty women of perimenopausal age who were diagnosed with RV/UTI and 50 age-matched healthy controls were enrolled. The urogenital and intestinal microbiota were analyzed via 16S ribosomal RNA gene sequencing by collecting samples from the mouth, anus, urine, cervix, and upper and lower vaginal ends. Among the microbiota of healthy perimenopausal women, the mouth had the highest richness, whereas the anus and mouth had the highest levels of diversity. Compared with those in healthy controls, in the microbiota of patients with RV/UTI, the evenness of the upper vaginal end, anus and cervix significantly increased, whereas the richness and diversity of the cervix significantly decreased. Lactobacillus accounted for 40.65% of the bacteria in the upper vaginal end and 39.85% of the bacteria in the lower vaginal end of healthy women of perimenopausal age, and there were no significant differences in Lactobacillus abundance among the patients with RV/UTI. The relative abundances of 54 genera and 97 species were significantly different between patients and healthy individuals, particularly in the cervix and urine. A total of 147 predicted pathways were significantly different between patients and healthy controls, with the microbiota of the anus exhibiting the greatest number of functional changes, followed by the urine microbiota. A random forest model composed of 16 genera in the lower vaginal end had the highest discriminatory power (AUC 81.48%) to predict RV/UTI. Conclusions Our study provides insight into the nature of the urogenital and intestinal microbiota in perimenopausal women, and reveals significant changes in the microbiota in patients with RV/UTI. This information will help characterize the relationship between the urogenital microbiota and RV/UTI, potentially aiding in the development of diagnostic and therapeutic strategies.